2020
DOI: 10.1073/pnas.1922867117
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk for skin autoimmunity impacts immune checkpoint blockade in bladder cancer

Abstract: PD-1 and PD-L1 act to restrict T cell responses in cancer and contribute to self-tolerance. Consistent with this role, PD-1 checkpoint inhibitors have been associated with immune-related adverse events (irAEs), immune toxicities thought to be autoimmune in origin. Analyses of dermatological irAEs have identified an association with improved overall survival (OS) following anti–PD-(L)1 therapy, but the factors that contribute to this relationship are poorly understood. We collected germline whole-genome sequenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 27 publications
3
45
0
Order By: Relevance
“…In addition to these two studies, Khan et al. recently published a retrospective analysis of clinical trial data of 220 bladder cancer patients ( 36 ). By means of whole genome sequencing they calculated polygenic risk scores for skin autoimmunity and found that psoriasis-associated polygenic risk scores were correlated to dermal irAE development (p < 0.05).…”
Section: Biomarkersmentioning
confidence: 99%
“…In addition to these two studies, Khan et al. recently published a retrospective analysis of clinical trial data of 220 bladder cancer patients ( 36 ). By means of whole genome sequencing they calculated polygenic risk scores for skin autoimmunity and found that psoriasis-associated polygenic risk scores were correlated to dermal irAE development (p < 0.05).…”
Section: Biomarkersmentioning
confidence: 99%
“…For example, Arbour et al reported that baseline GC equivalent to more than 10 mg prednisolone per day was associated with significantly poorer overall survival on multivariate analysis in patients with NSCLC (hazard ratio, 1.66; p < .001) [48]. Genetic variants partly explain the risk of autoimmune conditions that are treated with systemic steroids, such as RA [51], and in turn, such variants are associated with enhanced responsiveness to ICI [52]. This potentially confounding issue may partly explain contradictory findings regarding the association between baseline GC and ICI response, which has not been consistently demonstrated in all patient cohorts [53].…”
Section: Clinical Studies Relating To Coadministration Of Glucocorticmentioning
confidence: 99%
“…2-Deoxy-2-(18F)fluoro- D -glucose positron emission tomography/computed tomography performed during the treatment for restaging and/or response assessment can also reveal a wide range of IrAEs, (e.g., sarcoidosis-like syndrome, thyroiditis, hypophysitis, enterocolitis, interstitial pneumonitis, pancreatitis, and arthritis) with an accuracy of 83% ( 58 , 59 ). Authors recently reported that shared genetic factors impact risk for IrAEs and survival on immunotherapy in BC ( 60 ).…”
Section: Response Evaluationmentioning
confidence: 99%